Excessive Salt Intake Among Hypertensive Patients in Nepal: A Multicenter Observational Study - Acharya, Suman; Shrestha, Suraj; Kharel, Sanjeev; Neupane, Ashru; Khadka, Naresh Bahadur; Bhattarai, Anjan; Sigdel, Mahesh Raj; Singh, Dibya (Nepalese Heart Journal, 2026)
Background and Aims: Dietary salt is a modifiable risk factor for hypertension and cardiovascular diseases. The World Health Organisation recommends salt restriction to